7 - Ambiguities in the making of an African Medicine: clinical trials of Sutherlandia frutescens (L.) R.Br 1(Lessertia frutescens). - Diana Gibson, (African Sociological Review, 2011)
This paper attends to the large and heterogenous array of people and things that come togetherin the making of a medicinal plant, Sutherlandia frutescens (lessertia frutescens) as an Af- rican medicine through clinical trials. it is a messy, contested and ambiguous process and is constantly being revised and is always open to surprises and the possibility of failure. i use Sutherlandia to introduce some of the issues that complicate the landscapes of knowledge in South Africa in relation to phytomedicines and pharmaceuticals.